Transforming cities into sustainable and healthy territories starts with the “Culture of water”: learning from traditional peoples and communities of the Carapitanga river basin - Borges, Júlia; Gallo, Edmundo; Teixeira, Simonne (Frontiers in Environmental Science, 2024)
The manuscript titled "Transforming Cities into Sustainable and Healthy Territories Begins with the 'Culture of Water': Learning from Traditional Peoples and Communities of the Carapitanga River Basin" presents an innovative and relevant perspective for addressing water disparities and socioecological challenges in urban contexts, aligning comprehensively with the scope of the journal "Possible Nature(s) in Urban Spaces: Plurality and Agency to Tackle Socio-Ecological Challenges." This study is in direct harmony with the highlighted themes of the journal, encompassing Society-Nature relations, socioecological challenges, and Viable Socio-ecological Futures. By contributing ideas on regenerative cultures and sustainable futures, we believe our work can enrich the discourse promoted by the journal. The inclusion of this manuscript will broaden understanding of Water Governance, potentially contributing to the discussion on the importance of Water Culture for balancing the Hydrosocial Cycle in the construction of sustainable urban futures.